The American experiment : dialogues on a dream - Rubenstein, David M. (Simon & Schuster, 2021)
Pulitzer Prize-winning historians, diplomats, music legends and sports giants explore the grand American experiment in democracy, culture, innovation and ideas, revealing the setbacks, suffering, invention, ingenuity, and social movements that continue to shape our vision of what America is and what it can be.